The Role of Law Enforcement and Government Policies in Combating Air Pollution for a Sustainable Environment - Rahayu, Alya Maya Khonsa; Triwanto, Triwanto; Arantxha, Syifa Azzahra Nada; Astuti, Risma Yulia (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Air pollution is a significant environmental issue with severe consequences for human health and ecosystems. In Indonesia, particularly in major cities, high levels of air pollution pose a serious threat to public health and quality of life. The primary contributors include emissions from motor vehicles, industrial activities, and forest fires. However, law enforcement against polluters remains weak, and protection for victims is inadequate. This study examines law enforcement efforts aimed at protecting victims of air pollution and the government’s role in fostering a cleaner environment. A normative legal research method with a qualitative approach was employed. The findings highlight the urgent need to strengthen regulations, improve institutional coordination, and implement policies that effectively reduce pollution. Additionally, public awareness must be enhanced to ensure sustainable air quality and long-term environmental preservation.